2008
DOI: 10.1103/physrevb.77.085210
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of small compact self-interstitial clusters in crystalline silicon

Abstract: We have determined the atomic structure and formation energies of small, compact self-interstitial clusters ͑I n , n ഛ 10͒ in Si using a combination of Metropolis Monte Carlo, tight binding molecular dynamics, and density functional theory calculations. We present predicted local-minimum configurations for compact selfinterstitial clusters with n = 5 -10, together with well-defined smaller clusters ͑n ഛ 4͒ for comparison. The cluster formation energies per interstitial exhibit strong minima at n = 4 and 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 45 publications
4
43
2
Order By: Relevance
“…There are also a few small agglomerates of tetra-Is with 8, 12, 16 Is and so on [11], which precisely coincide with the local minima observed in Fig. 1.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…There are also a few small agglomerates of tetra-Is with 8, 12, 16 Is and so on [11], which precisely coincide with the local minima observed in Fig. 1.…”
supporting
confidence: 79%
“…Particularly in Si, there has been substantial experimental [2][3][4][5][6][7] and theoretical [8][9][10][11][12][13][14] work aimed at unraveling both the structure and properties of defects and their interaction with dopants. It is now well accepted that ion implantation generates a large self-interstitial (I) supersaturation, and that Is tend to aggregate in defect clusters that follow an Ostwald ripening (OR) process driven by the reduction of defect formation energies [8].…”
mentioning
confidence: 99%
“…Comparing the formation energies of small, compact clusters to DFT estimates in Ref. 7 further demonstrate that these empirical potentials are able to at least qualitatively capture much of the general picture associated with self-interstitial clustering, if not the precise thermodynamic properties.…”
Section: B Higher Temperatures With No Compressionmentioning
confidence: 99%
“…The various predicted structures were found to be in excellent structural agreement with microscopy observations and electronic-structure calculations. [2][3][4][5][6][7] Overall, the three different potentials employed, namely, the environment-dependent interatomic potential ͑EDIP͒, 8 Tersoff, 9 and Stillinger-Weber ͑SW͒, 10 all predicted consistent overall trends, leading to a qualitatively coherent picture for some aspects of selfinterstitial clustering in silicon. In particular, it was found that cluster morphology is sensitively dependent on both the temperature and stress within the lattice.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] The calculated energy hierarchy and the interstitial densities in Table I imply that for extended defects, rodlike ͕311͖ defects are initially favored. If the reaction barrier is not too high and the temperature is high enough to thermally activate the transformation, rodlike defects can evolve into Frank loops that are more stable and compact for a large number of interstitials.…”
Section: Implications For Growthmentioning
confidence: 94%